TISSUE CULTURE AND PLANT REGENERATION OF PRUNUS CAMPANULATA - Y. H. Zhang; J. D. Rong; Y. Fu; L. G. Chen; L. Y. Chen; Y.S. Zheng (Journal of Animal and Plant Sciences, 2015)
This study used the tender shoot of Prunus campanulata Maxim. of the current year as explants for the induction and rapid propagation of adventitious buds. The results showed that the bud induction rate peaked at 94.44% after treatment with Murashige and Skoog medium (MS) +2.0 mg L-1 6-benzyladenine (6-BA) + 0.1 mg L-1 naphthalene acetic acid (NAA). The multiplication coefficient was 7.44 after treatment with MS +3.0 mg L-1 6-BA + 0.01 mg L-1 NAA + 30 g L-1 sucrose. The combination of MS + 0.01 mg L-1 NAA + 0.3 mg L-1 gibberellic acid had the best growth-promoting effects (seedlings grew well; 2-4 cm high). The treatment of 1/2 MS + 1.0 mg L-1 indole-3-butyric acid + 0.5 mg L-1 IAA + 20 g L -1 sucrose had a rooting percentage of 82.35% in which the plants grew well with fast rooting and lengths of 3-4 cm. Treatment consisting of 1/2 MS +1.5 mg L-1 ABT one rooting powder (ABT1) + 20 g L-1 sucrose had the highest rooting percentage (93.05%) and growth. The matrix of vermiculite and perlite (1:1) was optimal for transplantation with a survival rate of up to 94.07%. This study involved the optimal mediums and culture conditions, all of which were significant for industrialized breeding and seedling production.
Keywords: Prunus campanulata Maxim.; tissue culture; micropropagation